IMPLEMENTASI AKUNTANSI KEUANGAN DALAM MENYUSUN LAPORAN KEUANGAN PADA UMKM BASRENG (BAKSO GORENG) - Azizah, Anisa Nur; Putri, Dwi Rencani; Yanti, Irma (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The existence of accounting in MSME activities can help and facilitate business actors to find out profits and decide what steps to take. This study aims to determine the application of accounting in these micro, small and medium enterprises. This study is a type of descriptive qualitative research with data collection conducted through indirect interviews. Micro, Small and Medium Enterprises (MSMEs) are the most dominant Micro, Small and Medium Enterprises (MSMEs) in Indonesia and the world. Micro, Small and Medium Enterprises (MSMEs) are growing rapidly and can be one of the pillars of the economy, especially in Indonesia. The government has issued Micro, Small and Medium Enterprise Accounting Standards (SAK EMKM) which is a simplification of general accounting standards, to help developing MSMEs in preparing their financial reports. This study uses a qualitative descriptive approach. Data comes from two sources. Sources of information include primary information collected directly through observation and interviews, as well as secondary information obtained from notes and photos about the company profile based on accounting standards such as journals and cash flow accounting when making financial reports. However, SAK EMKM in financial reporting has not been fully implemented or compiled comprehensively.